2010
DOI: 10.1016/j.molonc.2010.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of VEGF‐dependent transendothelial migration of cancer cells by bevacizumab

Abstract: Cancer progression is often associated with the formation of malignant effusions. Vascular endothelial growth factor (VEGF) is a major regulator of vascular permeability and has been implicated as mediator of tumor progression. We examined the production and secretion of VEGF(165) in various primary cancer cells derived from malignant effusions, and the role of exogenous VEGF165 as a mediator of effusion formation. VEGF165 was constantly secreted by all cultured tumor cells in an mTOR‐dependent manner, as it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
(86 reference statements)
0
32
0
1
Order By: Relevance
“…35 In a recent study, high VEGF concentrations were shown to increase the permeability of the endothelial monolayer, which promotes cells transmigration. 28 Since MSC can differentiate into endothelial-like cells in vitro under high VEGF concentrations, 25 it is speculated that MSC may behave similarly. Indeed, CD34 + HC transmigration through the MSC monolayer was significantly up-regulated after pre-incubating the MSC layer with conditioned medium that contained a high concentration of VEGF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 In a recent study, high VEGF concentrations were shown to increase the permeability of the endothelial monolayer, which promotes cells transmigration. 28 Since MSC can differentiate into endothelial-like cells in vitro under high VEGF concentrations, 25 it is speculated that MSC may behave similarly. Indeed, CD34 + HC transmigration through the MSC monolayer was significantly up-regulated after pre-incubating the MSC layer with conditioned medium that contained a high concentration of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…28 In order to examine the effect of VEGF on the MSC monolayer we performed a HC-MSC transmigration assay. In brief, the confluent MSC monolayer was pre-incubated with conditioned medium from either the atmospheric oxygen or low oxygen co-culture with or without anti-VEGF antibodies, as described in the Design and Methods section.…”
Section: Vascular Endothelium Growth Factor-a Secretion By Mesenchymamentioning
confidence: 99%
“…First, we evaluated the potential effects of cilengitide on integrin-specific cell behavior, such as cell adhesion, cell spreading and cell migration in MDA-MB-231 breast cancer cells, the same cell line used in the study mentioned above. MDA-MB-231 breast cancer cells are characterized by high integrin αVβ5 and low αVβ3 expression [35,37]. As shown in Fig.…”
Section: Cilengitide Impairs Mda-mb-231 Breast Cancer Cell Behaviormentioning
confidence: 94%
“…However, these studies did not address the biological rational for this observation. As the MDA-MB-231 breast cancer cell line used in these studies expresses αVβ3 integrins [35], any potential effect of cilengitide on osteoclasts was so far not shown. In this study, we aimed to investigate whether cilengitide reduces osteolytic lesions via inhibition of breast cancer cells or as speculated, via inhibition of osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…Cell migration was assayed in a modified boyden chamber system using transwell membranes (8 lm) (Nunc, Landenselbold, Germany) coated with gelatin, as described before [20]. Endothelial cells (2 Â 10 4 ) were added to the top chamber in the presence or absence of erlotinib, sorafenib or DMSO control.…”
Section: Angiogenesis Assaysmentioning
confidence: 99%